2010 IEEE International Conference on Acoustics, Speech and Signal Processing 2010
DOI: 10.1109/icassp.2010.5495503
|View full text |Cite
|
Sign up to set email alerts
|

Score normalization in playback attack detection

Abstract: The task of a playback attack detector (PAD) is to decide whether an incoming recording shares the same originating utterance as any of N stored recordings. All recordings are noisy channel-distorted versions of the same phrase uttered by the same person; the originating utterances of the N stored recordings are assumed to be distinct. The proposed approach makes a decision based on a set of N similarity scores which quantify the similarity between the incoming recording and each of the N stored recordings. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…A countermeasure for replay attack detection in the case of text-dependent ASV was reported in [36]. The approach is based upon the comparison of new access samples with stored instances of past accesses.…”
Section: Countermeasuresmentioning
confidence: 99%
“…A countermeasure for replay attack detection in the case of text-dependent ASV was reported in [36]. The approach is based upon the comparison of new access samples with stored instances of past accesses.…”
Section: Countermeasuresmentioning
confidence: 99%
“…Recently, due to the mass-market adoption of ASV techniques Nuance, 2013) and the awareness and simplicity of replay attacks, both industry (Nuance, 2013) and academia (Shang and Stevenson, 2010;Villalba and Lleida, 2011a,b;Wang et al, 2011) have shown an interest in developing replay attack countermeasures.…”
Section: Countermeasuresmentioning
confidence: 99%
“…The first approach to replay detection was reported in (Shang and Stevenson, 2010) in the context of a text-dependent ASV system using fixed pass-phrases. The detector is based upon the comparison of new access samples with stored instances of past access attempts.…”
Section: Countermeasuresmentioning
confidence: 99%
“…Besides, the algorithm was improved in [5] in which the spectral peaks are combined into pairs with a seed peak. This method, in [2][3][4][5], is only based on text-dependent speaker verification system and the efficiency of detection will significantly decrease When the number of request certification for client increase. 2) Detection algorithm based on the speech channel.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, though the same person says the same content at different times, the speech signals still have great randomness. In [2] and [3], a playback detector based on the random of speech sounds was designed to compare the verification recording with stored recording of past access attempts. Wu,in [4], adopted the same algorithm on the study of playback speech detection and extended the experimental samples.…”
Section: Introductionmentioning
confidence: 99%